Topological Properties on the Space of Diffeomorphism of Dynamical Systems of Flat Electroencephalography - Tan, Lit Ken; Tahir, Ahmad; Mohd Sham, Mohamad; Lee, Kee Quen (International Journal Series, 2016)
Electroencephalograph is one of the useful and favoured instruments in diagnosing various brain disorders especially in epilepsy due to its non-invasive characteristic and ability in providing wealthy information about brain functions. To study epilepsy more effectively, a flattening method called Flat Electroencephalography was invented to view EEG signals on the real plane for further analysis. This novel method is well known for its ability to preserves the orientation and magnitude of EEG sensors and signals. As such, it certainly contains affluent information about seizure process. Since both events of epileptic seizure and Flat EEG are continuous processes, its states connectivity will be explored topologically. Generally, this paper study the topological properties of Flat Electroencephalography. In addition, the topology on the space of diffeomorphism of the dynamical systems of Flat Electroencephalography will also be studied.